Bed of roses [videorecording (DVD)] - Slater, Christian; Masterson, Mary Stuart, 1966-; Adlon, Pamela, 1966-; Brolin, Josh; Goldenberg, Michael, 1965-; Goldenberg, Michael, 1965- (New Line Home Entertainment, 1999)
A business executive and a florist bond over their mutual need for company but, as their friendship grows, they must overcome their own fears and hesitations to make their relationship work.